Evaluation of postoperative pain in patients undergoing unilateral inguinal hernioplasty by Lichtenstein - Milioli Ferreira, Diogo; Franciss, Maurice (International Journal of Clinical Research, 2023)
Background: Lichtenstein’s surgery is the most recommended technique in the treatment of unilateral inguinal hernias in men, due to its simplicity, speed, pain-free, and almost unrestricted return to physical activities. The evidence indicates that work and leisure activities can be resumed, by most patients, in three to five days after laparoscopic or conventional hernioplasties, without the risk of recurrences or complications. Nevertheless, chronic pain is the most common postoperative complication affecting about 30% of patients regardless of the surgical technique used. Predictive factors for chronic pain are young age, female gender, preoperative pain level, and postoperative pain intensity. Aim: To evaluate the perception of postoperative pain in patients who have undergone unilateral elective inguinal hernioplasty using the Lichtenstein technique in order to define predictors of the development of chronic pain and to identify the average time to return to work and to normal physical activity. Methods: Analysis of electronic forms applied to patients that underwent elective unilateral inguinal hernia repair by Lichtenstein at a state hospital in a small town in the interior of Brazil. The statistical analyses were processed using the software Statistical Package for Social Sciences (SPSS) version 22.0. Results: Data from 38 participants were analyzed with an average of 41.45 (± 13.94) years. Most of them returned to work and to light physical activities 45 days after surgery. There was a positive correlation between the presence of pain 90 days after surgery and the development of chronic pain (Spearman correlation of 0,818 and p < 0.001). Conclusion: Despite the small sample of this study, it awakens us to the consequences that Lichtenstein surgery can trigger for patients with inguinal hernia and the importance of good management and evaluation of postoperative pain in order to improve the quality of life of these patients.